Sexually Transmitted Disease Partner Services Costs, Other Resources, and Strategies Across Jurisdictions to Address Unique Epidemic Characteristics and Increased Incidence. Issue 8 (August 2019) - Silverman, Rachel A.; Katz, David A.; Levin, Carol; Bell, Teal R.; Spellman, Dawn; St. John, Lisa; Manley Rodriguez, Evelyn; Golden, Matthew R.; Barnabas, Ruanne V.
Abstract : Background: Sexually transmitted disease (STD) partner services (PS) are a core component of STD programs. Data on costs are needed to support PS programming. Methods: In Washington State STD PS programs, disease intervention specialists (DIS) conduct telephone-based interviews and occasional field visits, offer expedited partner therapy to heterosexuals with gonorrhea or chlamydia, and promote human immunodeficiency virus (HIV) testing, preexposure prophylaxis, and HIV care. We conducted activity-based microcosting of PS, including: observational and self-reported time studies and interviews. We analyzed cost, surveillance, and service delivery data to determine costs per program outcomes. Results: In King, Pierce, and Spokane counties, respectively, DIS allocated 6.5, 6.4, and 28.8 hours per syphilis case and 1.5, 1.6, and 2.9 hours per gonorrhea/chlamydia case, on average. In 2016, each full-time DIS investigated 270, 268, and 61 syphilis and 1177, 1105, and 769 gonorrhea/chlamydia cases. Greater than 80% of syphilis cases in King and Pierce were among men who have sex with men versus 38% in Spokane. Disease intervention specialists spent 12% to 39% of their time actively interviewing cases and notifying partners (clients), and the remaining time locating clients, coordinating and verifying care, and managing case reports. Time spent on expedited partner therapy, HIV testing, and referrals to HIV treatment or preexposure prophylaxis, was minimal (<5 minutes per interview) at locations with resources outside PS staff. Program cost-per-interview ranged from US $527 to US $2210 for syphilis, US $219 to US $484 for gonorrhea, and US $164 to US $547 for chlamydia. Discussion: The STD PS resource needs depended on epidemic characteristics and program models. Integrating HIV prevention objectives minimally impacted PS-specific program costs. Results can inform program planning, future budget impact, and cost-effectiveness analyses. Abstract : Cost assessment of partner services for sexually transmitted diseases found high variability in activities and costs across Washington State health jurisdictions. Human immunodeficiency virus prevention and treatment interventions had minimal impact on program costs.Supplemental digital content is available in the text.